IMF Research Bulletin, September 2008. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2008)
IMF research summaries on global population aging and pension reform (by Mario Catalan) and on questions about decoupling (by M. Ayhan Kose); country study on the United States (by Koshy Mathai); listing of visiting scholars at the IMF during June-August 2008; listing of contents of Vol. 55 No. 3 of IMF Staff Papers; listing of recent IMF Working Papers; and a listing of recent external publications by IMF staff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet